Peningkatan Hasil Belajar Mahasiswa PGSD Materi Kecepatan Menggunakan Fast Trick - Nugraini, Frisca Anghi; Ramadhan, Fahmi Hasan (Nur Science Institute, 2023)
Background: Education is very important in the current era of globalization. The purpose of education is to grow and develop the potential of students to become individuals who have knowledge, skills, are independent, and are civilized. UMS PGSD students are expected to take various courses and achieve the desired competencies, including the Basic Science Concepts course. To improve learning outcomes, one alternative that can be done is to develop students' understanding using fast formulas or